Negative electrode sheet, all-solid-state battery, and electric device
Patent Information
- Application Number
- CN202611479220.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
AI Technical Summary
然而,硫化物固态电解质对水分极度敏感,负极片制备过程中引入的游离水会与其持续发生水解反应,生成硫化氢、氢氧化锂腐蚀性副产物
[0030]本发明实施例提供的负极片,在负极活性层中添加填料,填料包括氨基改性多孔材料和金属有机框架材料,且将填料的质量百分含量控制在1.5-6%。氨基改性多孔材料可以切断硫化物固态电解质水解的源头。金属有机框架材料可以阻断硫化氢的累积。通过两者功能互补,有助于在负极活性层中形成均匀分散的吸附位点网络,实现负极活性层中水分与硫化氢的协同捕获,同时维持硫化物固态电解质与负极活性物质之间良好的固固接触界面,确保锂离子传输通道和电子导电网络的畅通,使负极片兼具锂离子高效传导及腐蚀性副产物原位清除能力,在保持良好锂离子高效传导的基础上,有效提高循环寿命,有利于在不牺牲硫化物基全固态电池高容量的前提下,显著延长其循环寿命。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, specifically to a negative electrode sheet, an all-solid-state battery, and electrical equipment. Background Technology
[0002] Solid-state batteries, as a new generation of high-energy-density energy storage technology, are one of the core research directions in the fields of electric vehicles, energy storage systems, and consumer electronics. Silicon-based anode materials are widely considered to be the key to achieving high energy density in solid-state batteries because their specific capacity far exceeds that of traditional graphite anode materials.
[0003] In sulfide-based all-solid-state battery systems, a sulfide solid electrolyte is typically introduced into the active layer of the negative electrode to achieve rapid ion conduction within the negative electrode. However, sulfide solid electrolytes are extremely sensitive to moisture; free water introduced during the negative electrode fabrication process will continuously undergo hydrolysis with them, generating corrosive byproducts such as hydrogen sulfide and lithium hydroxide. These byproducts exist inside the negative electrode, leading to a sharp decrease in the cycle life of the all-solid-state battery.
[0004] Therefore, developing a negative electrode with a long cycle life has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] This invention provides a negative electrode sheet that utilizes the synergistic effect of amino-modified porous materials and metal-organic framework materials to enable the negative electrode sheet to have both high-efficiency lithium-ion conduction and in-situ removal of corrosive byproducts. While maintaining good high-efficiency lithium-ion conduction, it effectively improves cycle life and overcomes the defects of existing technologies.
[0006] The present invention also provides an all-solid-state battery that, while maintaining efficient lithium-ion conduction, effectively suppresses the erosion of the interface and active lithium by side reactions, and significantly extends cycle life.
[0007] The present invention also provides an electrical device that can meet the endurance requirements of high energy density power supplies in the fields of electric vehicles, energy storage systems and consumer electronics, and improve the reliability of the electrical device.
[0008] On one hand, the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector, the negative electrode active layer comprising a negative electrode active material, a sulfide solid electrolyte, and a filler, the filler comprising an amino-modified porous material and a metal-organic framework material; the mass percentage of the filler in the negative electrode active layer is 1.5-6%.
[0009] According to one embodiment of the present invention, the mass ratio of the amino-modified porous material to the metal-organic framework material is 1:3 to 3:1;
[0010] And / or, the amino-modified porous material has an amino grafting amount of 1.5-3.2 mmol / g, an average pore size of 1.8-3.2 nm, and a BET specific surface area of 400-1000 m². 2 / g;
[0011] And / or, the metal-organic framework material has a hydrogen sulfide adsorption capacity of 10-15 mmol / g, an average pore size of 1.0-1.3 nm, and a BET specific surface area of 740-950 m². 2 / g;
[0012] And / or, the metal-organic framework material includes M-MOF-74, wherein M includes at least one of nickel, cobalt, and iron.
[0013] According to one embodiment of the present invention, the amino-modified porous material includes at least one of amino-modified silicon-based material and amino-modified carbon-based material.
[0014] According to one embodiment of the present invention, the amino-modified silicon-based material comprises mesoporous silica and an aminosilane coupling agent grafted onto the mesoporous silica.
[0015] According to one embodiment of the present invention, the aminosilane coupling agent includes at least one of 3-aminopropyltriethoxysilane and N-2-aminoethyl-3-aminopropyltriethoxysilane.
[0016] According to one embodiment of the present invention, the mass percentage of the sulfide solid electrolyte in the negative electrode active layer is 8-20%;
[0017] And / or, the mass percentage of the negative electrode active material in the negative electrode active layer is 45-70%.
[0018] According to one embodiment of the present invention, the negative electrode active material includes a silicon-carbon material, the silicon-carbon material including porous silicon and a carbon coating layer covering at least a portion of the surface of the porous silicon.
[0019] According to one embodiment of the present invention, the thickness of the carbon coating layer in the silicon-carbon material is 2-10 nm;
[0020] And / or, the porous silicon in the silicon-carbon material has a particle size Dv50 of 100-250 nm and a porosity of 55-65%.
[0021] According to one embodiment of the present invention, the negative electrode active layer further includes a conductive agent, the conductive agent including a first conductive agent and / or a second conductive agent;
[0022] The first conductive agent comprises porous carbon, which includes mesopores and macropores. The macropores account for 15-45% of the total pore volume of the porous carbon. The main peak of the mesopores is located at 5.2 nm, and the main peak of the macropores is located at 85 nm.
[0023] The second conductive agent includes at least one of conductive graphite, conductive carbon black, and carbon nanotubes.
[0024] According to one embodiment of the present invention, the conductive agent includes a first conductive agent and a second conductive agent, wherein the mass ratio of the first conductive agent to the second conductive agent is 30:4 to 15:1;
[0025] And / or, the mass percentage of the conductive agent in the negative electrode active layer is 16-34%.
[0026] According to one embodiment of the present invention, the negative electrode active layer further includes a binder, wherein the mass percentage of the binder in the negative electrode active layer is 2-6%, and the binder includes a polyimide binder.
[0027] In another aspect, the present invention provides an all-solid-state battery, including the aforementioned negative electrode.
[0028] In another aspect, the present invention provides an electrical device including the aforementioned battery.
[0029] The implementation of this invention has at least the following beneficial effects:
[0030] The negative electrode sheet provided in this invention adds fillers to the negative electrode active layer. The fillers include amino-modified porous materials and metal-organic framework materials, and the mass percentage of the fillers is controlled at 1.5-6%. The amino-modified porous materials can cut off the source of hydrolysis of sulfide solid electrolytes. The metal-organic framework materials can block the accumulation of hydrogen sulfide. Through the complementary functions of the two, it helps to form a uniformly dispersed adsorption site network in the negative electrode active layer, realizing the synergistic capture of moisture and hydrogen sulfide in the negative electrode active layer. At the same time, it maintains a good solid-solid contact interface between the sulfide solid electrolyte and the negative electrode active material, ensuring the smooth flow of lithium-ion transport channels and electronic conductivity networks. This allows the negative electrode sheet to have both high-efficiency lithium-ion conduction and in-situ removal capabilities for corrosive byproducts. While maintaining good high-efficiency lithium-ion conduction, it effectively improves cycle life, which is beneficial to significantly extend the cycle life of sulfide-based all-solid-state batteries without sacrificing their high capacity. Detailed Implementation
[0031] To enable those skilled in the art to better understand the solutions of this invention, the following provides a more detailed description of this application. The specific embodiments listed below are merely descriptions of the principles and features of this invention; the examples are only for explaining the invention and are not intended to limit its scope. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this invention.
[0032] The inventors researched a sulfide-based all-solid-state battery system. The sulfide solid electrolyte introduced into the negative electrode active layer of the negative electrode is extremely sensitive to moisture. Free water introduced during the negative electrode fabrication process will continuously undergo hydrolysis with it, generating corrosive byproducts such as hydrogen sulfide and lithium hydroxide. These byproducts exist inside the negative electrode, and on the one hand, they corrode the solid-solid interface between the sulfide solid electrolyte and the negative electrode active material, generating non-conductive impurities (such as Li₂S and LiOH) at the interface, blocking lithium-ion transport channels and causing a surge in interface impedance. On the other hand, they also irreversibly consume active lithium, forming non-conductive lithium salt deposits, directly causing a precipitous decrease in the all-solid-state battery capacity, accompanied by battery swelling, a sharp reduction in cycle life, and other failure phenomena.
[0033] In existing negative electrode technologies, molecular sieves are often introduced into the active layer of the negative electrode to adsorb water and reduce the impact of moisture on the sulfide solid electrolyte. However, molecular sieves can only physically adsorb water and have extremely weak ability to capture hydrogen sulfide. Furthermore, as an inert impurity phase, molecular sieves can crowd out lithium-ion transport channels, leading to decreased conductivity. Existing negative electrode materials cannot effectively capture water and hydrogen sulfide, nor can they simultaneously achieve both high-efficiency lithium-ion conduction and in-situ removal of corrosive byproducts, while maintaining good lithium-ion conduction and effectively improving cycle life. Based on this, the inventors proposed the negative electrode material of this invention.
[0034] This invention provides a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector. The negative electrode active layer includes a negative electrode active material, a sulfide solid electrolyte, and a filler. The filler includes an amino-modified porous material and a metal-organic framework material. The mass percentage of the filler in the negative electrode active layer is 1.5-6%.
[0035] The negative electrode sheet provided in this invention incorporates fillers in the negative electrode active layer. These fillers include amino-modified porous materials and metal-organic framework materials. The amino groups in the amino-modified porous material preferentially immobilize free water through hydrogen bonding, making it difficult for water to continue contacting the surface of the sulfide solid electrolyte. This helps reduce adverse interfacial changes caused by water, cutting off the source of hydrolysis of the sulfide solid electrolyte. The unsaturated metal coordination sites in the metal-organic framework material can adsorb hydrogen sulfide, thereby fixing the hydrogen sulfide already generated in the system to the surface active centers, reducing the migration and diffusion of hydrogen sulfide within the negative electrode active layer, and blocking the accumulation of hydrogen sulfide. Through the functional complementarity of the amino-modified porous material and the metal-organic framework material, the synergistic capture of water and hydrogen sulfide in the negative electrode active layer is achieved. Meanwhile, amino-modified porous materials and metal-organic framework materials also have interconnected pore structures, making the water and hydrogen sulfide adsorption channels independent of the lithium ion transport channels. This can reduce the negative impact of the filler on the electrode conductivity and ion conduction performance, and has the ability to carry out high-efficiency lithium ion conduction and remove corrosive by-products in situ. While maintaining the good high-efficiency lithium ion conduction of the negative electrode, it can effectively improve the cycle life, which is beneficial to significantly extend the cycle life of sulfide-based all-solid-state batteries without sacrificing their high capacity.
[0036] Furthermore, controlling the filler mass percentage within the range of 1.5-6% ensures that the filler provides sufficient adsorption sites in the negative electrode active layer without excessively occupying lithium-ion migration space. This reduces the problem of insufficient effective sites for moisture and hydrogen sulfide capture in the negative electrode active layer due to an excessively low filler mass percentage (less than 1.5%), which hinders the continuous and stable functioning of the negative electrode throughout its lifespan. It also reduces the problem of filler crowding out the contact volume fraction between the sulfide solid electrolyte and the negative electrode active material due to an excessively low filler mass percentage (greater than 6%), affecting the continuity of ion channels and the electronic conductivity network. Within this range, the filler mass percentage helps form a uniformly dispersed adsorption site network in the negative electrode active layer, allowing the adsorption functions of the amino-modified porous materials and metal-organic framework materials for water and hydrogen sulfide to be fully utilized. Simultaneously, it maintains a good solid-solid interface between the sulfide solid electrolyte and the negative electrode active material, ensuring unobstructed lithium-ion transport channels and the electronic conductivity network, thereby significantly extending the cycle life of the all-solid-state battery while maintaining high capacity.
[0037] For example, the mass percentage of the filler in the above-mentioned highly active layer can be 1.5%, 2%, 4%, 6%, or any combination thereof.
[0038] It should be noted that the determination of the mass percentage of amino-modified porous materials can be achieved by first scraping off the negative electrode active layer from the surface of the negative electrode sheet and grinding it to obtain negative electrode material powder. Then, the total nitrogen content in the negative electrode material powder is determined by an elemental analyzer, and the mass percentage of amino-modified porous materials is calculated by combining the theoretical nitrogen content of pure amino-modified porous materials.
[0039] Specifically, the mass percentage of the amino-modified porous material can be determined according to the following procedure: 100±2 mg of negative electrode material powder is weighed in an argon glove box (H2O≤0.1ppm, O2≤0.1ppm), and then vacuum dried at 110℃ for 2 h to obtain the test sample. The total nitrogen (N) content of the test sample is then determined using a CHNS / O elemental analyzer (EA), and the mass percentage of the amino-modified porous material is calculated. Cross-validation is performed using thermogravimetric analysis.
[0040] The testing conditions for the CHNS / O elemental analyzer were as follows: combustion tube temperature 1050℃, reduction tube temperature 650℃, carrier gas He (99.999%), thermal conductivity detector (TCD), and calibration using acetanilide as the standard. Three parallel determinations were performed, and the relative standard deviation (RSD) of the three determinations was less than or equal to 2.5%.
[0041] The formula for calculating the mass percentage of amino-modified porous materials is: Mass percentage of amino-modified porous materials (%) = (C_N, measured / C_N, physical) × 100%.
[0042] Wherein, C_N, is the total nitrogen content in the test sample, and C_N, is the theoretical nitrogen content of the pure amino-modified porous material (calculated from the amount of grafting, e.g., a grafting amount of 1.8~2.4 mmol / g corresponds to a theoretical N content of 2.52~3.36 wt%). When the N element in the negative electrode material powder comes only from the amino-modified porous material, the conversion result is the actual mass fraction of the amino-modified porous material.
[0043] It should be noted that the mass percentage of metal-organic framework materials can be determined by first scraping off the negative electrode active layer from the surface of the negative electrode sheet and grinding it to obtain negative electrode material powder. Then, the mass percentage of metal-organic framework materials can be calculated by using ICP-OES (or ICP-MS) to trace characteristic metal elements.
[0044] Specifically, the mass percentage content of metal-organic framework materials (such as M-MOF-74, where M includes at least one of nickel, cobalt, and iron) can be determined according to the following procedure: Weigh 100±2 mg of the negative electrode material powder in an argon glove box (H2O≤0.1ppm, O2≤0.1ppm), then vacuum dry it at 110℃ for 2 h. Next, place it in a polytetrafluoroethylene microwave digestion vessel, add a mixed acid of HNO3:HCl:H2O2=3:1:1 (v / v), and then digest it in a sealed container at 180℃ for 20 min to obtain the sample to be tested. Then, determine the concentration of the characteristic metal element (M element) using ICP-OES (or ICP-MS). The formula for calculating the mass percentage content of the metal-organic framework material is: Mass percentage content of metal-organic framework material (%) = (C_M, measured / C_M, theoretical) × 100%.
[0045] Wherein, C_M,measured represents the content of element M in the test sample, and C_M,Theoretical represents the theoretical content of element M in pure metal-organic framework materials (e.g., Fe-MOF-74 is 35.8±0.5wt%, Ni-MOF-74 is 34.9±0.5wt%, and Co-MOF-74 is 34.5±0.5wt%).
[0046] In one possible embodiment, the negative electrode active layer is disposed on one side of the negative electrode current collector. In another possible embodiment, the negative electrode active layer is disposed on both sides of the negative electrode current collector.
[0047] In some embodiments, the mass ratio of the amino-modified porous material to the metal-organic framework material is 1:3 to 3:1, for example, it can be a range of 1:3, 1:2, 1:1, 2:1, 3:1, or any combination thereof. Controlling the mass ratio of the amino-modified porous material to the metal-organic framework material at 1:3 to 3:1 allows them to synergistically capture moisture and hydrogen sulfide, which helps to achieve a balance between cutting off the source of hydrolysis of sulfide solid electrolytes and blocking the accumulation of hydrogen sulfide. This effectively maintains interfacial stability and the retention of active lithium during long-term cycling, significantly improving the cycle life and capacity retention of the negative electrode.
[0048] In some embodiments, the amino-modified porous material has an amino grafting amount of 1.5-3.2 mmol / g, an average pore size of 1.8-3.2 nm, and a BET specific surface area of 400-1000 m². 2 / g. When the amount of amino grafting, average pore size, and BET surface area of the amino-modified porous material are within the above ranges, it is beneficial to improve the in-situ adsorption efficiency and adsorption capacity of the amino-modified porous material for free water. Under its synergistic effect, sufficient amino grafting provides abundant chemisorption sites, suitable particle size ensures its uniform dispersion in the negative electrode active layer, and reasonable pore size and specific surface area ensure that water molecules can quickly enter the pores and fully contact the amino groups, thereby achieving efficient and long-lasting free water capture and effectively blocking the hydrolysis pathway of sulfide solid electrolytes.
[0049] For example, the amount of amino grafting in the above-mentioned amino-modified porous material can be in the range of 1.5 mmol / g, 1.6 mmol / g, 1.8 mmol / g, 2 mmol / g, 2.1 mmol / g, 2.7 mmol / g, 3.0 mmol / g, 3.1 mmol / g, 3.2 mmol / g or any combination thereof.
[0050] For example, the average pore size of the above-mentioned amino-modified porous material can be in the range of 1.8 nm, 2 nm, 2.4 nm, 2.9 nm, 3 nm, 3.2 nm or any combination thereof.
[0051] For example, the BET specific surface area of the above-mentioned amino-modified porous material can be 400 m². 2 / g、420m 2 / g、450m 2 / g、500m 2 / g、550m 2 / g、600m 2 / g、650m 2 / g、700m 2 / g、750m 2 / g、800m 2 / g、850m 2 / g、890m 2 / g、900m 2 / g、980m 2 / g, 1000m 2 / g or a range consisting of any two of them.
[0052] It should be noted that the amount of amino grafting in amino-modified porous materials can be calculated by measuring the nitrogen content using an elemental analyzer; the average pore size and BET specific surface area are determined by nitrogen adsorption-desorption method (according to GB / T 19587-2017).
[0053] In some embodiments, the metal-organic framework material has a hydrogen sulfide adsorption capacity of 10-15 mmol / g, an average pore size of 1.0-1.3 nm, and a BET specific surface area of 740-950 m². 2 / g. When the hydrogen sulfide adsorption capacity, average pore size, and BET specific surface area of the metal-organic framework (MOF) are within the above-mentioned range, it is beneficial to improve the in-situ adsorption efficiency and adsorption capacity of the MOF for hydrogen sulfide. Under its synergistic effect, the sufficient hydrogen sulfide adsorption capacity reflects that it has a sufficient number of unsaturated metal coordination sites, which can effectively capture hydrogen sulfide molecules generated by hydrolysis; the appropriate particle size ensures its uniform dispersion in the negative electrode active layer and good contact with the sulfide solid electrolyte; and the reasonable micropore size and specific surface area are matched to ensure that hydrogen sulfide molecules can smoothly enter the pores to contact the unsaturated metal sites, and provide a sufficient active interface for the adsorption reaction. Thus, the MOF can establish a highly efficient chemical adsorption barrier inside the negative electrode, timely capture and fix the corrosive hydrogen sulfide generated by hydrolysis, block its erosion of the solid-solid interface and active lithium, and effectively ensure the cycle stability and safety of the sulfide-based all-solid-state battery.
[0054] For example, the hydrogen sulfide adsorption capacity of the metal-organic framework material can be in the range of 10 mmol / g, 10.1 mmol / g, 11 mmol / g, 12 mmol / g, 13 mmol / g, 14 mmol / g, 14.8 mmol / g, 15 mmol / g or any two of these ranges.
[0055] For example, the average pore size of the metal-organic framework material described above can be in the range of 1 nm, 1.1 nm, 1.2 nm, 1.3 nm or any two of these.
[0056] For example, the BET specific surface area of the above-mentioned metal-organic framework material can be 740 m². 2 / g、750m 2 / g、800m 2 / g、850m 2 / g、900m 2 / g、940m 2 / g、950m 2 / g or a range consisting of any two of them.
[0057] It should be noted that the hydrogen sulfide adsorption capacity of metal-organic framework materials can be determined by dynamic adsorption breakthrough experiment or static capacity method; the average pore size and BET specific surface area are determined by nitrogen adsorption-desorption method (according to GB / T 19587-2017).
[0058] In this embodiment of the invention, the amino-modified porous material includes at least one of amino-modified silicon-based material and amino-modified carbon-based material. These substances all contain amino groups, enabling them to preferentially capture free water in the sulfide solid electrolyte system, thereby cutting off the source of hydrolysis of the sulfide solid electrolyte. These substances also possess a porous structure, providing sufficient mass transfer channels and adsorption sites to ensure ion conduction channels within the negative electrode active layer.
[0059] In this embodiment of the invention, the amino-modified silicon-based material comprises mesoporous silica and an aminosilane coupling agent grafted onto the mesoporous silica. In the amino-modified silicon-based material, the mesoporous silica serves as a porous framework, providing sufficient space for the distribution of amino sites without significantly obstructing ion transport channels. The aminosilane coupling agent forms a stable chemical graft layer on the surface and inner walls of the pores of the mesoporous silica through a silanization reaction, uniformly anchoring the amino functional groups to the surface of the porous framework. Through the interaction between the mesoporous silica and the aminosilane coupling agent, the amino-modified silicon-based material possesses both rapid molecular transport capabilities and efficient surface chemisorption capabilities. This facilitates the establishment of a stable in-situ free water capture barrier within the negative electrode, inhibiting the hydrolysis reaction of the sulfide solid electrolyte from the source, and providing effective front-end protection for the hydrogen sulfide adsorption function of subsequent metal-organic framework materials.
[0060] In some embodiments, the aminosilane coupling agent includes at least one of 3-aminopropyltriethoxysilane and N-2-aminoethyl-3-aminopropyltriethoxysilane. The aminosilane coupling agent is used to silanize and graft onto the surface of mesoporous silica, forming a stable amino functional layer on the outer layer of the porous silica framework. This facilitates the uniform anchoring of amino functional groups to the inner walls of the pores, improving the chemisorption capacity for free water, while maintaining the permeability of the mesoporous structure, ensuring that water can quickly enter the pores and contact the amino groups, thereby guaranteeing water removal efficiency.
[0061] In this embodiment of the invention, the preparation method of amino-modified silicon-based material includes the following steps:
[0062] A template agent solution containing a template agent and a silicon source are mixed and then subjected to a hydrolysis-condensation reaction to obtain a silica sol precursor; wherein the pH value of the template agent solution is alkaline.
[0063] The silica sol precursor was subjected to hydrothermal crystallization and calcination treatment in sequence to obtain mesoporous silica.
[0064] Mesoporous silica, a first organic solvent, and an aminosilane coupling agent are mixed and then subjected to a grafting reaction to obtain an amino-modified silicon-based material.
[0065] The method for preparing amino-modified silicon-based materials provided in this invention involves forming a silicon dioxide framework with an ordered mesoporous structure using a template method, and then uniformly anchoring amino functional groups onto the inner walls and surface of the mesoporous silicon dioxide pores through a silanization grafting reaction. This results in amino-modified silicon-based materials possessing both high specific surface area, ordered mesoporous channels, and sufficient amino adsorption sites, enabling efficient capture of free water and thus improving their ability to remove impurities and stabilize interfaces in sulfide-based all-solid-state battery systems.
[0066] In some embodiments, the silicon source includes at least one of tetraethyl orthosilicate and methyl orthosilicate. Both tetraethyl orthosilicate and methyl orthosilicate, as silicon sources, can undergo hydrolysis and condensation under alkaline conditions, which is beneficial for forming mesoporous silica with regular structure and uniform pore size distribution, ensuring the uniformity of subsequent grafting and the orderliness of the mesoporous structure.
[0067] In some embodiments, the template agent includes at least one of hexadecyltrimethylammonium bromide and hexadecyltriethylammonium bromide. As template agents, hexadecyltrimethylammonium bromide and hexadecyltriethylammonium bromide can self-assemble into an ordered micelle array under alkaline conditions, guiding the deposition and condensation of silica precursors around them. After removal by calcination, regular and ordered mesoporous channels are formed, which is beneficial for obtaining mesoporous silica with high specific surface area and narrow pore size distribution.
[0068] In some embodiments, the mass ratio of silicon source to template agent is 1:(0.1-0.3), for example, it can be a range of 1:0.1, 1:0.2, 1:0.25, 1:0.3, or any combination thereof. Controlling the mass ratio of silicon source to template agent within the above range ensures that the amount of template agent is sufficient to form an ordered micelle template, guiding the uniform deposition of silicon source to form a regular mesoporous structure. Simultaneously, it reduces the risk of excessive template agent leading to excessively thin pore walls or framework structure collapse, providing sufficient reaction sites and unobstructed pore structures for subsequent grafting.
[0069] In some embodiments, the mass ratio of mesoporous silica to aminosilane coupling agent is 1:(0.6-1.5), for example, it can be a range of 1:0.6, 1:1, 1:1.5, or any combination thereof. Controlling the mass ratio of mesoporous silica to aminosilane coupling agent within the above range ensures sufficient silanization grafting on the surface and inner walls of the mesoporous silica channels, while reducing the risk of excessive aminosilane coupling agent leading to an overly thick grafted layer or pore blockage. This facilitates achieving high-density amino functionalization while maintaining the openness of the mesoporous structure.
[0070] In some embodiments, the pH of the template agent solution is 10-11, for example, a range consisting of 10, 10.5, 11, or any two of these. Controlling the pH of the template agent solution within this range ensures sufficient reactivity for the silicon source to fully hydrolyze and condense to form a continuous framework, while reducing the risk of structural collapse due to excessively rapid hydrolysis and condensation. Furthermore, within this range, it is beneficial to form mesoporous silica with a regular mesoporous structure and high specific surface area.
[0071] In this embodiment of the invention, the process of mixing a template agent solution containing a template agent and a silicon source and then carrying out a hydrolysis-condensation reaction includes: dissolving the template agent in water, then adjusting the pH value to alkaline to obtain a template agent solution, and then adding a silicon source to the template agent solution to carry out a hydrolysis-condensation reaction.
[0072] The process first dissolves the template agent and adjusts it to a suitable alkaline environment, then introduces the silicon source, which is then uniformly hydrolyzed and condensed in the presence of the template agent micelles, which is conducive to the formation of mesoporous silica with regular structure and ordered channels.
[0073] In some embodiments, the hydrolysis-condensation reaction is carried out at a temperature of 30-50°C for 1-3 hours. By controlling the temperature and time of the hydrolysis-condensation reaction within the above range, the silicon source can be fully hydrolyzed and orderly assembled with the template agent micelles to form a well-structured silica sol precursor. At the same time, it can reduce structural defects caused by excessively high temperature or long time in the hydrolysis-condensation reaction, which would lead to excessively rapid hydrolysis-condensation. This is beneficial to ensuring the ordered mesoporous structure and integrity of the subsequent hydrothermal crystallization product.
[0074] For example, the temperature of the above hydrolysis-condensation reaction can be a range of 30°C, 40°C, 50°C or any combination thereof.
[0075] For example, the time for the above hydrolysis-condensation reaction can be a range of 1h, 2h, 3h or any combination thereof.
[0076] In some embodiments, the hydrothermal crystallization treatment is carried out at a temperature of 100-120°C for 20-30 hours. Controlling the temperature and time of the hydrothermal crystallization treatment within the above range can promote the rearrangement and ordering of the silicon-oxygen network, resulting in a more regular mesoporous structure and denser pore walls in the mesoporous silica.
[0077] For example, the temperature of the above hydrothermal crystallization treatment can be a range of 100°C, 110°C, 120°C or any combination thereof.
[0078] For example, the time for the above hydrothermal crystallization treatment can be a range of 20h, 25h, 30h or any combination thereof.
[0079] In some embodiments, the calcination treatment is carried out at a temperature of 500-600°C for 4-8 hours. Controlling the temperature and time of the calcination treatment within the above range not only removes the template agent but also opens stable mesoporous channels and retains a high specific surface area, thereby achieving the shaping of the mesoporous silica pore structure and providing sufficient surface sites for subsequent grafting.
[0080] For example, the temperature of the calcination treatment described above can be a range of 500°C, 550°C, 600°C, or any combination thereof.
[0081] For example, the calcination time can be a range of 4h, 6h, 8h or any combination thereof.
[0082] In some embodiments, the grafting reaction temperature is 50-120°C, and the time is 4-24 hours. Controlling the temperature and time of the grafting reaction within the above range allows the aminosilane coupling agent to fully enter the pores and undergo a condensation reaction with the surface silanol groups, forming a stable siloxane bond grafted layer. At the same time, it can reduce the risk of the aminosilane coupling agent self-condensing or the grafted layer becoming too thick and clogging the pores due to excessively high grafting reaction temperature or excessively long time. This is beneficial for forming a uniform and stable amino functional layer on the surface of mesoporous silica and the inner wall of the pores, which is conducive to maintaining the unobstructed flow of the mesoporous silica structure and ensuring a balance between free water capture efficiency and lithium ion transport performance.
[0083] For example, the temperature of the grafting reaction can be a range of 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or any combination thereof.
[0084] For example, the grafting reaction time can be a range of 4h, 8h, 10h, 13h, 15h, 18h, 20h, 24h or any combination thereof.
[0085] In this embodiment of the invention, the metal-organic framework material includes M-MOF-74, where M includes at least one of nickel, cobalt, and iron. Nickel, cobalt, and iron are all divalent metal ions with unsaturated coordination capabilities, which can form a stable MOF-74 topology with organic ligands. The exposed unsaturated metal coordination sites directionally adsorb and fix hydrogen sulfide molecules, weakening the diffusion and accumulation of hydrogen sulfide in the negative electrode active layer.
[0086] It should be noted that M-MOF-74 is a type of metal-organic framework material with the same topological structure, formed by the self-assembly of divalent metal ions and organic ligands through coordination bonds. Its framework has a one-dimensional honeycomb-like channel structure. Here, MOF is an abbreviation for Metal-Organic Framework, 74 is the number of this type of metal-organic framework structure, and M is a placeholder for the metal site, indicating the divalent metal ion occupying the framework node.
[0087] In this embodiment of the invention, the preparation method of the metal-organic framework material includes the following steps:
[0088] Metal salts, organic ligands, and a second organic solvent are mixed and subjected to a solvothermal reaction to obtain metal-organic framework precursors.
[0089] The metal-organic framework precursor is subjected to solvent displacement treatment with a third organic solvent, followed by drying to obtain the metal-organic framework material; wherein the boiling point of the third organic solvent is lower than that of the second organic solvent.
[0090] The method for preparing metal-organic framework materials provided in this invention involves a solvothermal reaction that allows metal ions and organic ligands to self-assemble into a metal-organic framework precursor with a periodic pore structure. A low-boiling-point third organic solvent is then used to replace and remove the high-boiling-point second organic solvent within the pores. After drying, unsaturated metal coordination sites are exposed, maintaining the integrity of the metal-organic framework material's crystal structure and the unobstructed flow of its pores. This enables efficient capture of hydrogen sulfide, thereby improving the negative electrode's ability to remove hydrogen sulfide and effectively suppressing interfacial impedance growth and active lithium consumption, which is beneficial for improving the cycle life of all-solid-state batteries.
[0091] It should be noted that by replacing the high-boiling-point second organic solvent in the pores with a low-boiling-point third organic solvent, the pore blockage caused by the residue of the high-boiling-point second organic solvent can be reduced, allowing open metal sites and microporous structures to be exposed, thereby improving the adsorption activity and pore availability of metal-organic framework materials.
[0092] In some embodiments, the metal salt includes a metal nitrate, which includes at least one of nickel nitrate, cobalt nitrate, and iron nitrate. The metal nitrate can fully release metal ions to participate in the coordination reaction, which is beneficial for forming a uniform metal-organic framework precursor in the solvothermal reaction, thereby improving the nucleation uniformity and crystal integrity of the MOF-74 framework.
[0093] In some embodiments, the organic ligand includes 2,5-dihydroxyterephthalic acid. 2,5-dihydroxyterephthalic acid contains two carboxyl groups and two phenolic hydroxyl groups, and the multiple coordinating atoms can form polydentate coordination with metal ions, which is beneficial for forming a framework with a honeycomb-like porous structure.
[0094] In some embodiments, the second organic solvent includes at least one of N,N-dimethylformamide, N,N-diethylformamide, and N-methylpyrrolidone. These substances are all high-boiling-point polar solvents with good solubility for metal nitrates and organic ligands. They can provide a homogeneous reaction medium for the coordination assembly of metal ions and ligands in solvothermal reactions, which is beneficial for the formation of metal-organic framework precursors with high crystallinity and uniform crystal size.
[0095] In some embodiments, the third organic solvent includes at least one of ethanol, methanol, and acetone. These substances are all low-boiling-point polar solvents, which can effectively replace the high-boiling-point second organic solvent remaining in the channels and are easily removed completely during subsequent drying.
[0096] In some embodiments, the mass ratio of organic ligand to metal salt is (3-6):1, for example, a range of 3:1, 4:1, 5:1, 6:1, or any combination thereof. Controlling the mass ratio of organic ligand to metal salt within this range reduces the increase of byproducts or pore structure defects caused by excess metal salt. Furthermore, within this range, it is beneficial to maintain the ordered connection of metal nodes, thereby forming a metal-organic framework material with a higher specific surface area and more open metal sites, thus improving the adsorption capacity for hydrogen sulfide impurities.
[0097] In some embodiments, the amount of the third organic solution is 10-15 times the volume of the metal-organic framework precursor, for example, it can be a range of 10 times, 13 times, 15 times or any two of these.
[0098] In some embodiments, the solvothermal reaction temperature is 90-120°C, and the time is 12-24 hours. Controlling the temperature and time of the solvothermal reaction within the above range allows the metal ions and organic ligands to fully coordinate and assemble to form a complete crystal structure, while reducing the risk of excessive crystal growth or impurity phase formation caused by excessively high solvothermal reaction temperature or time.
[0099] For example, the temperature of the above-mentioned solvothermal reaction can be a range of 90°C, 100°C, 110°C, 120°C or any combination thereof.
[0100] For example, the time for the above-mentioned solvothermal reaction can be a range of 12h, 14h, 16, 18h, 20h, 22h, 24h or any combination thereof.
[0101] In some embodiments, the drying process is carried out at a temperature of 110-130°C for 8-16 hours. Controlling the drying temperature and time within the above range can effectively remove residual third organic solvents from the pores and expose unsaturated metal sites, thereby reducing the risk of structural collapse caused by excessively high drying temperatures or excessively long drying times.
[0102] For example, the temperature of the drying process described above can be a range of 110°C, 120°C, 130°C, or any combination thereof.
[0103] For example, the drying time described above can be a range of 8h, 10h, 12h, 14h, 16h or any combination thereof.
[0104] In this embodiment of the invention, the mass percentage of the sulfide solid electrolyte in the negative electrode active layer is 8-20%, for example, it can be 8%, 10%, 15%, 20%, or any combination thereof. By controlling the mass percentage of the sulfide solid electrolyte within the above range, the sulfide solid electrolyte can form a continuous lithium-ion transport network in the negative electrode active layer and maintain sufficient contact area with the negative electrode active material, thereby shortening the lithium-ion migration path and reducing the interface impedance. This is beneficial for maintaining the high energy density and structural integrity of the negative electrode active layer while ensuring ion conduction efficiency.
[0105] In this embodiment of the invention, the mass percentage of the negative electrode active material in the negative electrode active layer is 45-70%, for example, it can be 45%, 50%, 60%, 65%, 70%, or any combination thereof. Controlling the mass percentage of the negative electrode active material within the above range ensures that the negative electrode active layer has a sufficient proportion of active material to guarantee the high capacity of the all-solid-state battery, while reserving space for the addition of sulfide solid electrolyte and other functional components. This results in the negative electrode sheet having better lithium storage capacity, interface stability, and cycle performance.
[0106] The negative electrode active layer is centered on the lithium storage substrate and reserves necessary space for the sulfide solid electrolyte and other functional components, thereby maintaining the stability of the conductive network and structure while ensuring a high specific capacity. If this ratio is too low, there will be insufficient active sites and a decrease in energy density; if it is too high, there will be insufficient sulfide solid electrolyte and conductive phase, resulting in limited ion diffusion.
[0107] In this embodiment of the invention, the negative electrode active material includes a silicon-carbon material, which comprises porous silicon and a carbon coating layer covering at least a portion of the surface of the porous silicon. Porous silicon, as the primary lithium storage active material, provides high capacity. The carbon coating layer, attached to the surface of the porous silicon, can buffer the volume expansion of the porous silicon during charging and discharging, reduce the pulverization and shedding of the negative electrode active material, and improve electron conduction, thus enhancing the structural stability and rate performance of the negative electrode active layer.
[0108] In some embodiments, the thickness of the carbon coating layer in the silicon-carbon material is 2-10 nm, for example, it can be a range of 2 nm, 3.2 nm, 4 nm, 6 nm, 8 nm, 9.8 nm, 10 nm, or any combination thereof. By controlling the thickness of the carbon coating layer within the above range, the carbon coating layer can form a uniform and continuous coating structure, effectively buffering the volume expansion of porous silicon, while reducing the obstruction of lithium-ion diffusion by an excessively thick carbon coating layer, which is beneficial for achieving a balance between protecting porous silicon and maintaining fast charge and discharge capability.
[0109] In some embodiments, the porous silicon in the silicon-carbon material has a particle size Dv50 of 100-250 nm and a porosity of 55-65%. By controlling the particle size of the porous silicon within the above range, the porous silicon has a suitable particle size to facilitate uniform dispersion and shorten the lithium-ion diffusion path. At the same time, the sufficient porosity provides internal buffer space for the volume expansion of the porous silicon, reduces the pulverization of the silicon-carbon material, and is beneficial to improving the cycle stability and structural integrity of the negative electrode active layer.
[0110] For example, the particle size Dv50 of the porous silicon can be a range of 100nm, 150nm, 200nm, 250nm or any two of these.
[0111] For example, the porosity of the porous silicon can be in the range of 55%, 60%, 65%, or any combination thereof.
[0112] In this embodiment of the invention, the method for preparing silicon-carbon material includes the following steps:
[0113] Porous silicon, a fourth organic solvent, and an organic carbon precursor are mixed and spray-dried to obtain a solid substance.
[0114] Silicon-carbon materials are obtained by carbonizing solid materials in an inert gas atmosphere.
[0115] The method for preparing silicon-carbon materials provided in this invention involves uniformly combining porous silicon with an organic carbon precursor through spray drying, followed by carbonization treatment to pyrolyze the organic carbon precursor into a carbon coating layer. This achieves uniform coating of the porous silicon with the carbon coating layer, enabling the silicon-carbon material to effectively buffer the volume expansion of the porous silicon and maintain its structural integrity during charging and discharging. It also provides a continuous electron conduction path, which is beneficial for improving the cycle life of all-solid-state batteries.
[0116] In some embodiments, the organic carbon precursor includes at least one of phenolic resin and polyvinylpyrrolidone. Both phenolic resin and polyvinylpyrrolidone, after carbonization, can form a carbon coating layer with good electrical conductivity and mechanical strength, effectively buffering the volume expansion of porous silicon during charging and discharging and improving its electronic conductivity.
[0117] In some embodiments, the mass ratio of porous silicon to organic carbon precursor is 1:(0.1-0.3), for example, it can be a range of 1:0.1, 1:0.15, 1:0.2, 1:0.3, or any combination thereof. Controlling the mass ratio of porous silicon to organic carbon precursor within the above range allows the organic carbon precursor to coat the porous silicon and form a continuous and uniform carbon coating layer after carbonization. This effectively buffers the volume expansion of porous silicon during charging and discharging and provides an electron conduction pathway, which is beneficial for achieving a balance between protecting the porous silicon and maintaining high capacity.
[0118] In some embodiments, the carbonization treatment temperature is 600-900°C, and the time is 2-6 hours. By controlling the carbonization temperature and time within the above range, the organic carbon precursor can be fully pyrolyzed and carbonized to form a dense carbon coating layer with good electrical conductivity. At the same time, it can reduce the risk of excessive graphitization or structural defects caused by excessively high carbonization temperature or excessively long carbonization time. Moreover, within the above range, it is beneficial to form silicon-carbon materials with uniform carbon coating and stable structure.
[0119] For example, the temperature of the carbonization process described above can be a range of 600°C, 650°C, 700°C, 800°C, 850°C, 900°C or any combination thereof.
[0120] For example, the carbonization time described above can be a range of 2h, 3h, 4h, 5h, 6h or any combination thereof.
[0121] In this embodiment of the invention, the negative electrode active layer further includes a conductive agent, which includes a first conductive agent and / or a second conductive agent;
[0122] The first conductive agent includes porous carbon, which includes mesopores and macropores. The macropores account for 15-45% of the total pore volume of the porous carbon. The main peak of the mesopores is located at 5.2 nm, and the main peak of the macropores is located at 85 nm.
[0123] The second conductive agent includes at least one of conductive graphite, conductive carbon black, and carbon nanotubes.
[0124] The conductive agent forms an electron transport network in the negative electrode active layer. The first conductive agent is porous carbon, in which the interconnection of mesopores and macropores facilitates the rapid transport of lithium ions, reduces solid-solid interface impedance, and also provides buffer space for the volume expansion of the negative electrode active material during charging and discharging, thus improving cycle life. The second conductive agent includes at least one of conductive graphite, conductive carbon black, and carbon nanotubes, which can fill the gaps between the porous carbon framework and the negative electrode active material, forming a point-line combined local conductive network, which helps to improve electron conduction while maintaining high ion conduction efficiency.
[0125] Furthermore, mesopores, as the main channels for rapid lithium-ion transport, can shorten the diffusion path of lithium ions from the sulfide solid electrolyte to the surface of the negative electrode active material, which is beneficial to reducing concentration polarization and thus improving rate performance. At the same time, macropores, as buffer spaces for volume expansion, can effectively accommodate the volume expansion of the negative electrode active material during charging and discharging, which can reduce particle pulverization and electrode structure damage caused by stress concentration. This is beneficial to maintaining the structural stability of the negative electrode sheet while ensuring high ion conduction efficiency, thereby extending cycle life.
[0126] For example, the porous carbon described above includes mesopores and macropores, and the ratio of macropores to the total pore volume of the porous carbon can be a range of 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any combination thereof.
[0127] It should be noted that the pore size distribution of porous carbon can be characterized using a combination of gas adsorption and mercury porosimetry. The pore size distribution of micropores (<2 nm) and mesopores (2~50 nm) can be analyzed using nitrogen adsorption-desorption isotherms (according to GB / T19587-2017 and GB / T 21650.2-2008), while the pore size distribution and macropore volume of macropores (>50 nm) can be determined using mercury porosimetry (according to GB / T 21650.1-2008). The ratio of macropores to the total pore volume of porous carbon is calculated from the pore volume of each pore size range measured by mercury porosimetry. Specifically, the formula for calculating the ratio of macropores to the total pore volume of porous carbon is: Ratio of macropores to the total pore volume of porous carbon (%) = (Macropore volume / (Macropore volume + Micropore volume + Micropore volume)) × 100%. Each sample is tested in triplicate, and the results are taken as the arithmetic mean, with a relative standard deviation of less than or equal to 3.5%.
[0128] In some embodiments, the conductive agent includes a first conductive agent and a second conductive agent, with a mass ratio of 30:4 to 15:1, for example, a range of 30:4, 18:2, 22.5:2, 220:2, 15:1, or any combination thereof. Controlling the mass ratio of the first and second conductive agents within this range allows for the formation of a continuous and stable electron transport main channel and an expansion buffer space for the negative electrode active material through a high proportion of porous carbon. An appropriate amount of the second conductive agent fills the gaps between the first conductive agent and the negative electrode active material, forming supplementary conductive contacts. Together, they form a complete conductive network, which helps to maintain high electron conduction efficiency while reducing the blockage of ion channels by the second conductive agent, thus achieving a balance between conductivity and ion transport efficiency.
[0129] In some embodiments, the mass percentage of the conductive agent in the negative electrode active layer is 16-34%, for example, it can be a range of 16%, 22%, 30%, 34%, or any combination thereof. Controlling the mass percentage of the conductive agent within this range allows it to form a continuous and stable electron transport network in the negative electrode active layer, ensuring efficient electron conduction within the negative electrode active layer. It also reduces the risk of excessive conductive agent content compressing the effective contact area between the sulfide solid electrolyte and the negative electrode active material, weakening the continuity of lithium-ion transport. Furthermore, within this range, it is beneficial to maintain high energy density and ion conduction performance of the negative electrode active layer while ensuring electron conduction efficiency.
[0130] In this embodiment of the invention, the negative electrode active layer further includes a binder, the binder in the negative electrode active layer having a mass percentage of 2-6%, and the binder includes a polyimide binder.
[0131] Polyimide binders possess high mechanical strength and good heat resistance, effectively bonding the components in the negative electrode active layer and maintaining the structural integrity of the negative electrode sheet during the volume expansion of the negative electrode active material. By controlling the mass percentage of the binder within the aforementioned range, the overall density and structural retention of the negative electrode active layer can be improved without significantly sacrificing ion migration efficiency.
[0132] For example, the mass percentage of the binder in the negative electrode active layer can be 2%, 4%, 6%, or any combination thereof.
[0133] This invention provides a method for preparing a negative electrode sheet, comprising the following steps:
[0134] A negative electrode slurry containing negative electrode active material, sulfide solid electrolyte and filler is coated on at least one side of the negative electrode current collector, and then subjected to drying, rolling and baking treatments in sequence to obtain a negative electrode sheet.
[0135] The method for preparing the negative electrode sheet provided in this invention involves coating, drying, rolling, and baking to uniformly distribute the negative electrode slurry and form a dense negative electrode active layer, thereby obtaining the negative electrode sheet. This method helps to ensure the structural consistency of the negative electrode sheet and is suitable for large-scale production.
[0136] In some embodiments, the drying process includes: heating the coated negative electrode current collector to 50-70°C and drying it for 1-4 hours, then continuing to heat it to 90-110°C and drying it for 8-12 hours.
[0137] The segmented heating and drying process removes most of the solvent at 50-70℃, which reduces cracking and component migration caused by rapid solvent evaporation. Then, deep drying at 90-110℃ further removes residual solvent, which is conducive to the formation of a uniform, crack-free negative electrode active layer and ensures the structural integrity and component distribution uniformity of the negative electrode sheet.
[0138] For example, the temperature at which the coated negative electrode current collector is heated can be a range of 50°C, 60°C, 70°C, or any combination thereof.
[0139] For example, the drying time after heating the coated negative electrode current collector to 50-70°C can be a range of 1h, 2h, 4h, or any combination thereof.
[0140] For example, the temperature at which the temperature is further increased can be a range of 90°C, 100°C, 110°C, or any two of these.
[0141] For example, the drying time after the temperature is raised to 90-110°C can be a range of 8h, 10h, 20h, or any combination thereof.
[0142] In some embodiments, the baking treatment is carried out at a temperature of 180-220°C for 12-20 hours. Controlling the temperature and time within this range effectively removes residual moisture from the negative electrode, reducing the hydrolysis reaction of the sulfide solid electrolyte caused by free water during the operation of the all-solid-state battery. This helps ensure the interfacial stability and electrochemical performance of the sulfide all-solid-state battery.
[0143] For example, the temperature of the baking process described above can be a range of 180°C, 200°C, 220°C, or any combination thereof.
[0144] For example, the baking time can be a range of 12h, 18h, 20h or any combination thereof.
[0145] This invention provides an all-solid-state battery, including the aforementioned negative electrode. This all-solid-state battery, using the aforementioned negative electrode, effectively suppresses the erosion of the interface and active lithium by side reactions while maintaining efficient lithium-ion conduction, significantly extending cycle life and balancing high energy density with long-cycle stability. It is suitable for electric vehicles and energy storage systems with high requirements for cycle stability and safety.
[0146] This invention provides an electrical device including the aforementioned battery. By employing the all-solid-state battery, which combines high capacity and long cycle life, as its power source, this device can meet the range requirements of high-energy-density power supplies in electric vehicles, energy storage systems, and consumer electronics. Simultaneously, it reduces the frequency of device replacement due to performance degradation of the all-solid-state battery, thereby lowering the total lifecycle cost and improving the reliability of the electrical device.
[0147] The electrical equipment in the embodiments of the present invention can be conventional electrical equipment in the art, such as electric vehicles, power tools, portable electronic devices (e.g., mobile phones, laptops), energy storage systems (e.g., home energy storage cabinets, grid energy storage stations), medical devices (e.g., portable monitors), and drones, etc., and there are no particular limitations.
[0148] The present invention will be further described below through specific embodiments.
[0149] Example 1
[0150] This embodiment 1 provides a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active layer disposed on one side of the negative electrode current collector.
[0151] This embodiment 1 provides a method for preparing a negative electrode sheet, including the following steps:
[0152] S1. The amino-modified silicon-based material contains amino groups. The amino grafting amount of the amino-modified silicon-based material is 2.4 mmol / g, the average pore size is 2.4 nm, and the BET specific surface area is 610 m². 2 / g. The preparation method of amino-modified silicon-based materials is as follows:
[0153] S10. Add 2.5 g of hexadecyltrimethylammonium bromide to 120 mL of deionized water to obtain a template agent solution. Then adjust the pH of the template agent solution to 10.5 with 25% ammonia water. Add 10 g of tetraethyl orthosilicate to the template agent solution and mix well. Then heat to 40 °C and perform hydrolysis and polycondensation reaction for 2 h to obtain the silica sol precursor.
[0154] S11. The silica sol precursor is heated to 110℃ and subjected to hydrothermal crystallization treatment for 24 hours. After the hydrothermal crystallization treatment, it is filtered to obtain a solid product. Then, the solid product is heated to 550℃ and calcined for 6 hours to obtain mesoporous silica.
[0155] S12. Mesoporous silica was dispersed in 80 mL of anhydrous ethanol, and 3-aminopropyltriethoxysilane was added (the amount of 3-aminopropyltriethoxysilane was such that the mass ratio of mesoporous silica to aminosilane coupling agent was 1:1.5). The mixture was then thoroughly mixed, and the temperature was raised to 60 °C. The grafting reaction was carried out for 12 h. After the grafting reaction was completed, the mixture was filtered, and the resulting solid product was washed three times with anhydrous ethanol. The washed solid product was then vacuum dried at 80 °C for 12 h to obtain the amino-modified silicon-based material.
[0156] S2. The metal-organic framework material is Ni-MOF-74. The hydrogen sulfide adsorption capacity of the metal-organic framework material is 11.8 mmol / g, the average pore size is 1.05 nm, and the BET specific surface area is 820 m². 2 / g. The preparation method of metal-organic framework materials is as follows:
[0157] S21. Dissolve 1g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and 0.3g of 2,5-dihydroxyterephthalic acid in 25mL of N,N-dimethylformamide, then heat to 100℃ and react solvothermically for 16h. After the solvotherm reaction is completed, filter the solution and wash the resulting solid product three times with N,N-dimethylformamide to obtain the metal-organic framework precursor.
[0158] S22. The metal-organic framework precursor is immersed in anhydrous ethanol (the amount of anhydrous ethanol is 10 times the volume of the metal-organic framework precursor) for solvent replacement treatment. The anhydrous ethanol is replaced every 8 hours during the solvent replacement treatment, and the total solvent replacement treatment time is 48 hours. After the solvent replacement treatment is completed, it is vacuum dried at 120°C for 10 hours to obtain the metal-organic framework material.
[0159] The ammonium salt solution was then transferred to a dialysis bag with a molecular weight cutoff of 3500 Da, using deionized water as the dialysate (the dialysate was placed outside the dialysis bag, and the volume of dialysate was 20 times the volume of the ammonium salt solution). Dialysis was performed for 24 hours, with the dialysate being replaced every 8 hours. After dialysis, the retained solution in the dialysis bag was collected. 50 mL of ethanol was then added to the retained solution for sedimentation.
[0160] S3. The silicon-carbon material comprises porous silicon and a carbon coating layer covering at least a portion of the surface of the porous silicon, the carbon coating layer having a thickness of 6 nm. The preparation method of the silicon-carbon material is as follows:
[0161] S31. Disperse 2g of porous silicon (particle size Dv50 of porous silicon is 250nm and porosity is 65%) in 30mL of anhydrous ethanol, add 0.3g of phenolic resin (carbon residue of phenolic resin is 60%) to obtain a mixture, and then spray dry the mixture to obtain a solid substance.
[0162] S32. Under an argon atmosphere, the solid material is heated to 700°C and carbonized for 3 hours to obtain silicon-carbon material.
[0163] S4. Under an argon atmosphere, the amino-modified silicon-based material and the metal-organic framework material are mixed, and then dry-milled at 400 r / min for 1.5 h to obtain the mixture. Then, the mixture is vacuum-dried at 200℃ for 6 h to obtain the filler.
[0164] The mass ratio of amino-modified silicon-based material to metal-organic framework material is 1:1.
[0165] Under an argon atmosphere, silicon-carbon materials, a sulfide solid electrolyte (lithium phosphorus-sulfur-chlorine, Li6PS5Cl), fillers, and a first conductive agent (the first conductive agent is porous carbon, which includes mesopores and macropores, with macropores accounting for 28% of the total pore volume, the main peak of mesopores located at 5.2 nm, and the main peak of macropores located at 85 nm; the BET specific surface area of the porous carbon is 780 m²) were tested. 2 / g, the total pore volume of porous carbon is 2.15cm³. 3 The mixture of a styrene-butadiene block copolymer (with an outer diameter of 15 nm and an aspect ratio of 600) and a second conductive agent (multi-walled carbon nanotubes) was then ball-milled at 300 r / min for 3 h to obtain a mixed powder. A hydrophobic binder (styrene-butadiene-styrene block copolymer with a weight-average molecular weight of 200,000 and a styrene content of 30 wt%) and anhydrous toluene were then added to the mixed powder and mixed thoroughly to obtain a negative electrode slurry.
[0166] The negative electrode slurry comprises, by mass percentage, 60% silicon-carbon material, 10% sulfide solid electrolyte, 4% filler, 20% first conductive agent, 2% second conductive agent, and 4% hydrophobic binder. The total solid content of the negative electrode slurry is 25%.
[0167] The negative electrode slurry is coated onto the surface of the carbon-coated copper foil current collector. The coated copper foil current collector is then heated to 60°C and dried for 0.5 hours, followed by further heating to 100°C and drying for 12 hours. The dried carbon-coated copper foil current collector is then rolled. Finally, the rolled carbon-coated copper foil current collector is vacuum dried at 120°C for 12 hours to obtain the negative electrode sheet.
[0168] Example 2
[0169] This embodiment 2 is basically the same as embodiment 1, except that:
[0170] In step S4, the mass ratio of amino-modified silicon-based material to metal-organic framework material is 2:1.
[0171] Example 3
[0172] This embodiment 3 is basically the same as embodiment 1, except that:
[0173] In step S4, the mass ratio of amino-modified silicon-based material to metal-organic framework material is 3:1.
[0174] Example 4
[0175] This embodiment 4 is basically the same as embodiment 1, except that:
[0176] In step S4, the mass ratio of amino-modified silicon-based material to metal-organic framework material is 1:2.
[0177] Example 5
[0178] This embodiment 5 is basically the same as embodiment 1, except that:
[0179] In step S4, the mass ratio of amino-modified silicon-based material to metal-organic framework material is 1:3.
[0180] Example 6
[0181] This embodiment 6 is basically the same as embodiment 1, except that:
[0182] In step S4, based on the total mass of solid components in the negative electrode slurry, the mass percentage of silicon carbon material is 60%, the mass percentage of sulfide solid electrolyte is 10%, the mass percentage of filler is 1.5%, the mass percentage of the first conductive agent is 22.5%, the mass percentage of the second conductive agent is 2%, and the mass percentage of hydrophobic binder is 4%.
[0183] Example 7
[0184] This embodiment 7 is basically the same as embodiment 1, except that:
[0185] In step S4, based on the total mass of solid components in the negative electrode slurry, the mass percentage of silicon carbon material is 60%, the mass percentage of sulfide solid electrolyte is 10%, the mass percentage of filler is 6%, the mass percentage of the first conductive agent is 18%, the mass percentage of the second conductive agent is 2%, and the mass percentage of hydrophobic binder is 4%.
[0186] Example 8
[0187] This embodiment 8 is basically the same as embodiment 1, except that:
[0188] In step S4, based on the total mass of solid components in the negative electrode slurry, the mass percentage of silicon-carbon material is 70%, the mass percentage of sulfide solid electrolyte is 8%, the mass percentage of filler is 4%, the mass percentage of the first conductive agent is 15%, the mass percentage of the second conductive agent is 1%, and the mass percentage of hydrophobic binder is 2%.
[0189] Example 9
[0190] This embodiment 9 is basically the same as embodiment 1, except that:
[0191] In step S4, based on the total mass of solid components in the negative electrode slurry, the mass percentage of silicon carbon material is 45%, the mass percentage of sulfide solid electrolyte is 11%, the mass percentage of filler is 4%, the mass percentage of the first conductive agent is 30%, the mass percentage of the second conductive agent is 4%, and the mass percentage of hydrophobic binder is 6%.
[0192] Example 10
[0193] This embodiment 10 is basically the same as embodiment 1, except that:
[0194] In step S4, based on the total mass of solid components in the negative electrode slurry, the mass percentage of silicon carbon material is 55%, the mass percentage of sulfide solid electrolyte is 20%, the mass percentage of filler is 4%, the mass percentage of the first conductive agent is 15%, the mass percentage of the second conductive agent is 2%, and the mass percentage of hydrophobic binder is 4%.
[0195] Example 11
[0196] This embodiment 11 is basically the same as embodiment 1, except that:
[0197] The metal-organic framework material is Co-MOF-74. The metal-organic framework material has a hydrogen sulfide adsorption capacity of 10.2 mmol / g, an average pore size of 1.02 nm, and a BET specific surface area of 790 m². 2 / g.
[0198] In the preparation method of metal-organic framework materials, in step S21, an equal amount of molybdenum nitrate pentahydrate is used to replace nickel nitrate hexahydrate.
[0199] Example 12
[0200] This embodiment 12 is basically the same as embodiment 1, except that:
[0201] The metal-organic framework material is Fe-MOF-74, which has a hydrogen sulfide adsorption capacity of 10.5 mmol / g, an average pore size of 1.10 nm, and a BET specific surface area of 780 m². 2 / g.
[0202] In the preparation method of metal-organic framework materials, in step S21, an equal amount of ferric nitrate nonahydrate is used to replace nickel nitrate hexahydrate.
[0203] Example 13
[0204] This embodiment 13 is basically the same as embodiment 1, except that:
[0205] The amino-modified silicon-based material contains amino groups. The amino grafting amount of the amino-modified silicon-based material is 2.9 mmol / g, the average pore size is 2.0 nm, and the BET specific surface area is 510 m². 2 / g.
[0206] In the preparation method of amino-modified silicon-based materials, in step S12, 3-aminopropyltriethoxysilane is added (the amount of 3-aminopropyltriethoxysilane satisfies the mass ratio of mesoporous silica to aminosilane coupling agent of 1:1.5), mixed evenly, and then heated to 110℃ for grafting reaction for 24h.
[0207] Example 14
[0208] This embodiment 14 is basically the same as embodiment 1, except that:
[0209] The amino-modified silicon-based material contains amino groups. The amino grafting amount of the amino-modified silicon-based material is 1.8 mmol / g, the average pore size is 2.7 nm, and the BET specific surface area is 695 m². 2 / g.
[0210] In the preparation method of amino-modified silicon-based materials, in step S12, 3-aminopropyltriethoxysilane is added (the amount of 3-aminopropyltriethoxysilane satisfies the mass ratio of mesoporous silica to aminosilane coupling agent of 1:0.6), mixed evenly, and then heated to 60℃ for grafting reaction for 4h.
[0211] Example 15
[0212] This embodiment 15 is basically the same as embodiment 1, except that:
[0213] The amino-modified silicon-based material contains amino groups. The amino grafting amount of the amino-modified silicon-based material is 1.6 mmol / g, the average pore size is 3.2 nm, and the BET specific surface area is 890 m². 2 / g.
[0214] In the preparation method of amino-modified silicon-based materials, in step S10, the amount of hexadecyltrimethylammonium bromide is adjusted to 1g.
[0215] Example 16
[0216] This embodiment 16 is basically the same as embodiment 1, except that:
[0217] The amino-modified silicon-based material contains amino groups. The amino grafting amount of the amino-modified silicon-based material is 3.1 mmol / g, the average pore size is 1.8 nm, and the BET specific surface area is 420 m². 2 / g.
[0218] In the preparation method of amino-modified silicon-based materials, in step S10, the amount of hexadecyltrimethylammonium bromide is adjusted to 3g.
[0219] Example 17
[0220] This embodiment 17 is basically the same as embodiment 1, except that:
[0221] The amino-modified silicon-based material contains amino groups. The amino grafting amount of the amino-modified silicon-based material is 2.1 mmol / g, the average pore size is 2.6 nm, and the BET specific surface area is 580 m². 2 / g.
[0222] In the preparation method of amino-modified silicon-based materials, in step S10, 10g of tetraethyl orthosilicate is added to the template agent solution and mixed evenly. Then, the temperature is raised to 30°C and the hydrolysis and condensation reaction is carried out for 3 hours to obtain a silica sol precursor.
[0223] In step S11, the silica sol precursor is heated to 100°C and subjected to hydrothermal crystallization treatment for 30 hours. After the hydrothermal crystallization treatment, it is filtered to obtain a solid product. Then, the solid product is heated to 600°C and calcined for 8 hours to obtain mesoporous silica.
[0224] Example 18
[0225] This embodiment 18 is basically the same as embodiment 1, except that:
[0226] The amino-modified silicon-based material contains amino groups. The amino grafting amount of the amino-modified silicon-based material is 2.7 mmol / g, the average pore size is 2.2 nm, and the BET specific surface area is 650 m². 2 / g.
[0227] In the preparation method of amino-modified silicon-based materials, in step S10, 10g of tetraethyl orthosilicate is added to the template agent solution and mixed evenly. Then, the temperature is raised to 50℃ and the hydrolysis and polycondensation reaction is carried out for 1 hour to obtain the silica sol precursor.
[0228] In step S11, the silica sol precursor is heated to 120°C and subjected to hydrothermal crystallization treatment for 20 hours. After the hydrothermal crystallization treatment, it is filtered to obtain a solid product. Then, the solid product is heated to 500°C and calcined for 4 hours to obtain mesoporous silica.
[0229] Example 19
[0230] This embodiment 19 is basically the same as embodiment 1, except that:
[0231] The amino-modified silicon-based material was replaced with an equal mass of amino-modified carbon-based material. The amino-modified carbon-based material contained amino groups, and had an amino grafting amount of 2.1 mmol / g, an average pore size of 3.1 nm, and a BET specific surface area of 980 m². 2 / g.
[0232] The preparation method of amino-modified carbon-based materials is as follows:
[0233] S51. Take 10.0g of activated carbon (the particle size Dv50 of the activated carbon is 8μm, and the BET specific surface area is 1400m²). 2 The activated carbon ( / g) was placed in 120 mL of 5% hydrochloric acid, then heated to 60 °C and ultrasonically vibrated for 2 h at 60 °C. The mixture was then filtered, and the resulting solid product was washed with water until the pH of the filtrate was 7. The washed solid product was then vacuum dried at 105 °C for 12 h to obtain pretreated activated carbon.
[0234] S52. Pretreated activated carbon was dispersed in 200 mL of anhydrous ethanol, and 1.5 g of 3-aminopropyltriethoxysilane was added and mixed thoroughly. The mixture was then heated to 80 °C and the grafting reaction was carried out for 12 h. After the grafting reaction was completed, the mixture was filtered, and the resulting solid product was washed three times with anhydrous ethanol. The washed solid product was then vacuum dried at 60 °C for 24 h to obtain amino-modified silicon-based material.
[0235] Example 20
[0236] This embodiment 20 is basically the same as embodiment 1, except that:
[0237] The metal-organic framework material is Ni-MOF-74. The metal-organic framework material has a hydrogen sulfide adsorption capacity of 11.8 mmol / g, an average pore size of 1.05 nm, and a BET specific surface area of 820 m². 2 / g.
[0238] In the preparation method of metal-organic framework materials, in step S21, 1g of nickel nitrate and 0.3g of 2,5-dihydroxyterephthalic acid are dissolved in 25mL of N,N-dimethylformamide, and then the temperature is raised to 100℃ and the solvothermal reaction is carried out for 12h.
[0239] In step S22, after the solvent replacement treatment is completed, the product is then vacuum dried at a temperature of 130°C for 10 hours.
[0240] Example 21
[0241] This embodiment 21 is basically the same as embodiment 1, except that:
[0242] The metal-organic framework material is Ni-MOF-74, which has a hydrogen sulfide adsorption capacity of 10.4 mmol / g, an average pore size of 1.0 nm, and a BET specific surface area of 760 m². 2 / g.
[0243] In the preparation method of metal-organic framework materials, in step S21, 1g of nickel nitrate and 0.3g of 2,5-dihydroxyterephthalic acid are dissolved in 25mL of N,N-dimethylformamide, and then the temperature is raised to 120℃ and the solvothermal reaction is carried out for 24h.
[0244] In step S22, after the solvent replacement treatment is completed, the product is then vacuum dried at a temperature of 110°C for 16 hours.
[0245] Example 22
[0246] This embodiment 22 is basically the same as embodiment 1, except that:
[0247] The metal-organic framework material is Ni-MOF-74, which has a hydrogen sulfide adsorption capacity of 10.1 mmol / g, an average pore size of 1.0 nm, and a BET specific surface area of 740 m². 2 / g.
[0248] In the preparation method of metal-organic framework materials, in step S21, 0.9 g of nickel nitrate and 0.3 g of 2,5-dihydroxyterephthalic acid are dissolved in 25 mL of N,N-dimethylformamide.
[0249] Example 23
[0250] This embodiment 23 is basically the same as embodiment 1, except that:
[0251] The metal-organic framework material is Ni-MOF-74. The metal-organic framework material has a hydrogen sulfide adsorption capacity of 14.2 mmol / g, an average pore size of 1.2 nm, and a BET specific surface area of 920 m². 2 / g.
[0252] In the preparation method of metal-organic framework materials, in step S21, 1.8g of nickel nitrate and 0.3g of 2,5-dihydroxyterephthalic acid are dissolved in 25mL of N,N-dimethylformamide.
[0253] Example 24
[0254] This embodiment 24 is basically the same as embodiment 1, except that:
[0255] The silicon-carbon material includes porous silicon and a carbon coating layer covering at least a portion of the surface of the porous silicon, the carbon coating layer having a thickness of 3.2 nm.
[0256] In the preparation method of silicon-carbon material, in step S31, 2g of porous silicon (the particle size Dv50 of the porous silicon is 250nm and the porosity is 65%) is dispersed in 30mL of anhydrous ethanol, and 0.2g of phenolic resin (the residual carbon rate of the phenolic resin is 60%) is added to obtain a mixture.
[0257] In step S32, the solid material is heated to 650°C and carbonized for 3 hours.
[0258] Example 25
[0259] This embodiment 25 is basically the same as embodiment 1, except that:
[0260] The silicon-carbon material includes porous silicon and a carbon coating layer covering at least a portion of the surface of the porous silicon, the carbon coating layer having a thickness of 9.8 nm.
[0261] In the preparation method of silicon-carbon materials, in step S31, 2g of porous silicon (the particle size Dv50 of the porous silicon is 250nm and the porosity is 65%) is dispersed in 30mL of anhydrous ethanol, and 0.6g of phenolic resin (the residual carbon rate of the phenolic resin is 60%) is added to obtain a mixture.
[0262] In step S32, the solid material is heated to 850°C and carbonized for 6 hours.
[0263] Example 26
[0264] This embodiment 26 is basically the same as embodiment 1, except that:
[0265] The silicon-carbon material includes porous silicon and a carbon coating layer covering at least a portion of the surface of the porous silicon, the carbon coating layer having a thickness of 6 nm.
[0266] In the preparation method of silicon-carbon materials, in step S31, the particle size Dv50 of porous silicon is 100 nm and the porosity is 65%.
[0267] Example 27
[0268] This embodiment 27 is basically the same as embodiment 1, except that:
[0269] The silicon-carbon material includes porous silicon and a carbon coating layer covering at least a portion of the surface of the porous silicon, the carbon coating layer having a thickness of 6 nm.
[0270] In the preparation method of silicon-carbon materials, in step S31, the particle size Dv50 of porous silicon is 250 nm and the porosity is 55%.
[0271] Example 28
[0272] This embodiment 28 is basically the same as embodiment 1, except that:
[0273] In step S4, the first conductive agent is porous carbon, which includes mesopores and macropores. The macropores account for 15% of the total pore volume of the porous carbon. The main peak of the mesopores is located at 5.2 nm, and the main peak of the macropores is located at 85 nm.
[0274] Example 29
[0275] This embodiment 29 is basically the same as embodiment 1, except that:
[0276] In step S4, the first conductive agent is porous carbon, which includes mesopores and macropores. The macropores account for 45% of the total pore volume of the porous carbon. The main peak of the mesopores is located at 5.2 nm, and the main peak of the macropores is located at 85 nm.
[0277] Comparative Example 1
[0278] Comparative Example 1 is basically the same as Example 1, except that:
[0279] In step S4, based on the total mass of solid components in the negative electrode slurry, the mass percentage of silicon carbon material is 60%, the mass percentage of sulfide solid electrolyte is 10%, the mass percentage of filler is 0%, the mass percentage of the first conductive agent is 24%, the mass percentage of the second conductive agent is 2%, and the mass percentage of hydrophobic binder is 4%.
[0280] Comparative Example 2
[0281] Comparative Example 2 is basically the same as Example 1, except that:
[0282] In step S4, the metal-organic framework material is replaced with an equal mass of amino-modified silicon-based material.
[0283] Comparative Example 3
[0284] Comparative Example 3 is basically the same as Example 1, except that:
[0285] In step S4, the amino-modified silicon-based material is replaced with an equal mass of metal-organic framework material.
[0286] Comparative Example 4
[0287] Comparative Example 4 is basically the same as Example 1, except that:
[0288] In step S4, based on the total mass of solid components in the negative electrode slurry, the mass percentage of silicon carbon material is 60%, the mass percentage of sulfide solid electrolyte is 10%, the mass percentage of filler is 0.5%, the mass percentage of the first conductive agent is 23.5%, the mass percentage of the second conductive agent is 2%, and the mass percentage of hydrophobic binder is 4%.
[0289] Comparative Example 5
[0290] Comparative Example 5 is basically the same as Example 1, except that:
[0291] In step S4, based on the total mass of solid components in the negative electrode slurry, the mass percentage of silicon carbon material is 60%, the mass percentage of sulfide solid electrolyte is 10%, the mass percentage of filler is 8%, the mass percentage of the first conductive agent is 16%, the mass percentage of the second conductive agent is 2%, and the mass percentage of hydrophobic binder is 4%.
[0292] Comparative Example 6
[0293] Comparative Example 6 is basically the same as Example 1, except that:
[0294] In step S4, an equal mass of silica (silica with a particle size Dv50 of 2.0 μm, an average pore size of 6.0 nm, and a BET specific surface area of 500 m²) is used. 2 / g) Replace the packing.
[0295] Comparative Example 7
[0296] Comparative Example 7 is basically the same as Example 1, except that:
[0297] In step S4, an equal mass of aluminum oxide (aluminum oxide with a particle size Dv50 of 1.5 μm, an average pore size of 10.0 nm, and a BET specific surface area of 200 m²) is used. 2 / g) Replace the packing.
[0298] Test case
[0299] (a) Performance testing of packing material
[0300] The packing materials prepared in step S4 of Examples 1-29 and Comparative Examples 1-7 were taken respectively, and the water adsorption capacity and hydrogen sulfide adsorption capacity of the packing materials were tested. The test results are shown in Table 1.
[0301] 1. The method for testing the water adsorption capacity of the packing is as follows: Based on the dynamic constant humidity airflow method, a dynamic water vapor adsorption instrument is used to bring the dried packing into contact with the humid carrier gas until adsorption equilibrium is reached. The mass change of the packing is recorded in real time by a precision micro balance (graduation value of 0.01mg), and the water adsorption capacity of the packing is calculated.
[0302] Specifically, 150±5 mg of packing material was weighed and placed in the sample boat (quartz) of the dynamic water vapor adsorption instrument. The temperature was then raised to 100℃ and dried in high-purity argon gas (purity ≥99.999%, H2O ≤1ppm, flow rate 50mL / min) for 2 hours. The mass change of the packing material was recorded in real time until the mass change was less than 0.01 mg for 30 consecutive minutes. The weight of the dried packing material, m0, was recorded. The dried packing material was then transferred to the test chamber of the dynamic water vapor adsorption instrument, and an argon gas flow rate of 25℃ and 500ppm H2O (argon gas flow rate 50mL / min) was introduced. The mass change of the packing material was recorded in real time until the mass change was less than <0.01 mg for 60 consecutive minutes, at which point adsorption equilibrium was reached. The mass of the packing material after water adsorption equilibrium, m1, was recorded, and the water adsorption capacity (mmol / g) of the packing material was calculated.
[0303] The formula for calculating water adsorption capacity (mmol / g) is as follows:
[0304] Water adsorption capacity (mmol / g) = [(m1-m0) / 18.015] / m0.
[0305] Where 18.015 is the molar mass of H2O in g / mol; m0 is the weight of the dried packing material in g; and m1 is the mass of the packing material after water adsorption equilibrium in g.
[0306] 2. The test method for hydrogen sulfide adsorption capacity of the packing is as follows: Based on the fixed-bed breakthrough method, a fixed-bed adsorption reaction tube (quartz or 316L stainless steel, inner diameter 9mm, effective packing length 40mm) and an online H2S detector (electrochemical sensor or GC-TCD / FID, detection limit ≤0.1ppm, response time <10s) are used. The carrier gas containing H2S is continuously passed through the fixed-bed adsorption reaction tube, and the change in H2S concentration at the outlet is monitored online. The breakthrough curve is plotted and the hydrogen sulfide adsorption capacity of the packing is calculated by integration.
[0307] Specifically, 100±5 mg of packing material (m3) was weighed and loaded into a fixed-bed adsorption reaction tube. The tube was then fixed by filling both ends with quartz wool. The temperature was raised to 80℃ and dried in high-purity argon gas (purity ≥99.999%, H2O ≤1 ppm, flow rate 50 mL / min) for 2 hours, followed by cooling to 25℃. Then, an argon gas flow (flow rate 30 mL / min) at 25℃ with an H2S mass concentration of 100 ppm was introduced. At this point, the initial H2S concentration C0 of the argon gas flow was 100 ppm. The H2S concentration C at the outlet of the fixed-bed adsorption reaction tube was recorded in real time. out Until C out When / C0 ≥ 90%, the adsorption saturation point is determined. Plot the breakthrough curve and calculate the hydrogen sulfide adsorption capacity of the packing material by integration.
[0308] Among them, when C out / C0≥5% is defined as the adsorption breakthrough point, when C out / C0≥90% is the adsorption saturation point. The breakthrough curve is plotted as C. out / C0 changes over time.
[0309] The formula for calculating the hydrogen sulfide adsorption capacity (mmol / g) is as follows:
[0310] Hydrogen sulfide adsorption capacity (mmol / g) = [∫0ᵗ(C0-C out )×Fdt] / (m3×Vm).
[0311] Where C0 is the initial H2S concentration of the argon gas flow, in ppm, C out The concentration of H2S at the outlet of the fixed-bed adsorption reaction tube is ppm; F is the volumetric flow rate of argon gas, mL / min; t is the total test time, min; m3 is the mass of the packing material, g; Vm is the molar volume of argon gas under standard conditions (22.414 L / mol = 22414 mL / mol).
[0312] (II) Performance testing of symmetrical cells
[0313] The mixed powders obtained in step S4 of Examples 1-29 and Comparative Examples 1-7 were taken respectively, and then the mixed powders were assembled with SS to form symmetrical cells. The ionic conductivity of the symmetrical cells was then tested, and the test results are shown in Table 1.
[0314] Assembly of the symmetrical cell: 0.2g of mixed powder was placed in an argon glove box (argon glove box dew point ≤ -50℃, H2O content ≤ 0.1ppm, O2 content ≤ 0.1ppm), then the mixed powder was loaded into a mold with an inner diameter of 13.0mm, and then pressure-treated at 300MPa for 5min to form a 0.8mm thick disc, thus obtaining the negative electrode composite material. The negative electrode composite material was then sandwiched between two 316L stainless steel blocking electrodes (SS) to assemble a symmetrical cell with an electrode area of 1.33cm². 2 .
[0315] 1. The ionic conductivity test method is as follows: The ionic conductivity of the mixed powder is tested by AC impedance spectroscopy (EIS) combined with DC polarization method.
[0316] Specifically, the symmetrical cell was left to stand at 25°C for 30 minutes. Then, an electrochemical workstation was connected, and a sinusoidal AC voltage with an amplitude of 5–10 mV was applied to the symmetrical cell. A frequency scan was performed within the frequency range of 1 MHz to 0.1 Hz, and the impedance response at different frequencies was recorded to obtain the impedance spectrum (Nyquist plot). In the Nyquist plot, the impedance spectrum in the high-frequency region (1 MHz to 10 kHz) is a semi-circular arc. The intersection of this semi-circular arc with the left side of the real axis (Z' axis) is taken as the bulk resistance R. total And calculate the total conductivity σ total .
[0317] Total conductivity σ total The calculation formula is as follows:
[0318] σ total =L / (R total Calculate the total conductivity using the formula ×A).
[0319] Where, σ total R is the total conductivity, in S / cm; L is the thickness of the disc, in cm; total A is the bulk resistance, in Ω; A is the electrode area, in cm². 2 .
[0320] Then, a DC polarization voltage of 20mV is applied to the symmetrical cell and the current is continuously supplied until the current stabilizes (current change rate < 1% / min), and the steady-state current I is recorded. ss The electronic conductivity σe is calculated. Then, based on the parallel model of mixed conductors, the ionic conductivity σe is calculated. ion .
[0321] The formula for calculating electronic conductivity σe is as follows:
[0322] σe=(I ss ×L) / (U×A).
[0323] Where σe is the electronic conductivity, with units of S / cm; I ss 1 is the steady-state current in A; L is the thickness of the disc in cm; U is the DC polarization voltage in mV; A is the electrode area in cm².
[0324] Ionic conductivity σ ion The calculation formula is as follows:
[0325] σ ion =σ total -σe.
[0326] Where, σ ion σ is the ionic conductivity, measured in S / cm. total σe represents the total conductivity, in units of S / cm; σe represents the electronic conductivity, in units of S / cm.
[0327] (III) Performance Testing of All-Solid-State Batteries
[0328] Negative electrode sheets prepared in Examples 1-29 and Comparative Examples 1-7 were used respectively. These negative electrode sheets were then assembled with high-nickel ternary positive electrode sheets and a sulfide solid electrolyte layer to obtain an all-solid-state battery. The initial discharge specific capacity, capacity retention after 50 cycles, and battery gas expansion of the all-solid-state battery were then tested. The test results are shown in Table 1.
[0329] Assembly of all-solid-state batteries: Under an argon atmosphere: High-nickel ternary cathode active material (NCM811, chemical formula of NCM811 is LiNi) is added. 0.8 Co 0.1 Mn 0.1 O2), sulfide solid electrolyte (Li6PS5Cl), conductive agent (vapor-grown carbon fiber with an average diameter of 150 nm and an aspect ratio of 80), and polytetrafluoroethylene (PTFE) were mixed uniformly in a mass ratio of 70:20:8:2. The mixture was then repeatedly folded and rolled using a roller press to obtain a compaction density of 2.05 g / cm³. 3 The positive electrode active layer is formed by rolling and bonding the positive electrode active layer with carbon-coated aluminum foil using a roller press to obtain the positive electrode sheet. Then, under an argon atmosphere, the negative electrode sheet, the sulfide solid electrolyte layer (which includes a sulfide solid electrolyte, specifically Li6PS5Cl), and the positive electrode sheet are stacked in sequence to assemble an all-solid-state battery.
[0330] 1. Initial Discharge Specific Capacity Test: The all-solid-state battery was left to stand at 25℃ for 24 hours. Then, at 25℃, it was charged at a constant current of 0.1C to 4.25V, and then charged at a constant voltage of 4.25V until the current density reached 0.05C. Finally, it was discharged at a constant current of 0.1C to 2.4V, and the initial discharge capacity was recorded and the initial discharge specific capacity was calculated.
[0331] The formula for calculating the initial discharge specific capacity is as follows:
[0332] First discharge specific capacity (mAh / g) = First discharge capacity / Mass of negative electrode material in negative electrode sheet.
[0333] 2. The cycle capacity retention test method is as follows: The all-solid-state battery is placed at 25℃ for 24 hours. Then it is charged at a constant current of 1C to 4.25V, and then charged at a constant voltage of 4.25V until the current density is 0.05C. Then it is discharged at a constant current of 1C to 2.4V. The above charge-discharge cycle is repeated 500 times. The discharge capacity of the first cycle and the specific capacity of the 500th cycle are recorded, and the capacity retention rate after 500 cycles is calculated.
[0334] The formula for calculating the capacity retention rate after 500 cycles is as follows:
[0335] Capacity retention rate after 500 cycles (%) = (500th discharge capacity / 1st discharge capacity) × 100%.
[0336] 3. The battery swelling test method is as follows: The swelling condition of the battery is characterized by testing the thickness expansion rate of the all-solid-state battery.
[0337] Specifically, the all-solid-state battery was left to stand at 25°C for 2 hours. The initial thickness of the active area of the all-solid-state battery was measured at the center and four corners using a digital micrometer, and the average initial thickness d0 was calculated. Then, the all-solid-state battery was stored in an open circuit at 60°C for 7 days. The final thickness of the active area of the all-solid-state battery was then measured at the center and four corners using a digital micrometer, and the average final thickness d1 was calculated. The thickness expansion rate η was also calculated.
[0338] The formula for calculating the thickness expansion coefficient η is as follows:
[0339] η=(d1-d0) / d0×100%.
[0340] Where η is the thickness expansion rate, in %; d1 is the average final thickness of the all-solid-state battery, in mm; and d0 is the average initial thickness of the all-solid-state battery, in mm.
[0341] If η ≤ 2.0%, it is judged as no bloating; if 2.0% < η ≤ 5.0%, it is judged as slight bloating; if η > 5.0%, it is judged as significant bloating.
[0342] Table 1
[0343]
[0344] As shown in Table 1, compared with the comparative example, the negative electrode of the present invention exhibits good initial discharge specific capacity and superior capacity retention after 50 cycles. The initial discharge specific capacity is greater than 1500 mAh / g, and the capacity retention after 50 cycles is greater than 78%. Moreover, when the negative electrode is applied to the battery, the battery does not experience gas expansion. This indicates that the negative electrode of the present invention, by adding filler with a mass percentage of 1.5-6% to the negative electrode active layer, can suppress hydrolysis and hydrogen sulfide accumulation, reduce gas accumulation and battery gas expansion caused by by-product accumulation, reduce interfacial polarization and side reaction losses, improve interfacial stability and ionic conductivity, and enable the negative electrode to exhibit excellent electrochemical performance under long-cycle conditions.
[0345] Compared to Example 1, the negative electrode active layer of Comparative Example 1 did not contain any filler. The battery obtained in Comparative Example 1 exhibited a decrease in capacity retention and significant gas buildup after 50 cycles. This may be due to the continuous hydrolysis of the sulfide solid electrolyte by trace amounts of free water within the battery, generating hydrogen sulfide. The continuous accumulation of hydrogen sulfide erodes the solid-solid interface, gradually increasing the interfacial resistance and leading to increased irreversible consumption of active lithium, thus resulting in decreased capacity retention and battery gas buildup.
[0346] Compared to Example 1, the negative electrode active layer of Comparative Example 2 was filled with an amino-modified silicon-based material, while the negative electrode active layer of Comparative Example 3 was filled with a metal-organic framework material. Both Comparative Example 2 and Comparative Example 3 batteries exhibited a decrease in capacity retention after 50 cycles and slight gas buildup. This may be because adding only amino-modified silicon-based material or metal-organic framework material to the negative electrode active layer cannot effectively interrupt the hydrolysis and corrosion chain reaction. Residual hydrogen sulfide will continue to erode the solid-solid interface and consume active lithium, leading to decreased cycle performance and gas buildup. This also indicates that the synergistic effect of amino-modified silicon-based material and metal-organic framework material can continuously and effectively inhibit the hydrolysis reaction of sulfide solid electrolytes during cycling, reduce the accumulation of hydrogen sulfide, reduce the formation of interfacial byproducts, thereby reducing the rate of interfacial impedance growth, improving interfacial stability, effectively protecting active lithium, and thus improving battery cycle performance.
[0347] Compared to Example 1, the negative electrode active layer of Comparative Example 4 had a filler content of 0.5% by mass. The battery obtained in Comparative Example 4 exhibited a decrease in capacity retention and significant gas buildup after 50 cycles. This is likely because when the filler content is less than 1.5%, the number of active sites in the negative electrode active layer for capturing free water and adsorbing hydrogen sulfide is insufficient, making it difficult to effectively suppress the increase in interfacial impedance, thus leading to a decrease in capacity retention and battery gas buildup. In Comparative Example 5, the negative electrode active layer had a filler content of 8% by mass. The battery obtained in Comparative Example 5 showed a decrease in capacity retention after 50 cycles. This is likely because when the filler content is greater than 6%, excessive filler accumulation blocks ion transport channels, reducing ion migration rates, thereby reducing conductivity and the utilization rate of the negative electrode active material, resulting in decreased cycle performance.
[0348] Compared to Example 1, the negative electrode active layer of Comparative Example 6 was filled with silicon dioxide; the negative electrode active layer of Comparative Example 7 was filled with aluminum oxide. Both Comparative Example 6 and Comparative Example 7 showed a decrease in capacity retention after 50 cycles and significant gas buildup. This may be because ordinary silicon dioxide and aluminum oxide only physically adsorb a small amount of free water and cannot effectively adsorb hydrogen sulfide. Therefore, they cannot effectively inhibit the erosion of the solid-solid interface by hydrogen sulfide during cycling, leading to decreased cycle performance and battery gas buildup.
[0349] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode sheet, characterized in that, The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector. The negative electrode active layer includes a negative electrode active material, a sulfide solid electrolyte, and a filler. The filler includes an amino-modified porous material and a metal-organic framework material. The mass percentage of the filler in the negative electrode active layer is 1.5-6%. The metal-organic framework material includes M-MOF-74, where M includes at least one of nickel, cobalt, and iron.
2. The negative electrode sheet according to claim 1, characterized in that, The mass ratio of the amino-modified porous material to the metal-organic framework material is 1:3 to 3:1; And / or, the amino-modified porous material has an amino grafting amount of 1.5-3.2 mmol / g, an average pore size of 1.8-3.2 nm, and a BET specific surface area of 400-1000 m². 2 / g; And / or, the metal-organic framework material has a hydrogen sulfide adsorption capacity of 10-15 mmol / g, an average pore size of 1.0-1.3 nm, and a BET specific surface area of 740-950 m². 2 / g.
3. The negative electrode sheet according to claim 1, characterized in that, The amino-modified porous material includes at least one of amino-modified silicon-based materials and amino-modified carbon-based materials.
4. The negative electrode sheet according to claim 3, characterized in that, The amino-modified silicon-based material includes mesoporous silica and an aminosilane coupling agent grafted onto the mesoporous silica.
5. The negative electrode sheet according to claim 4, characterized in that, The aminosilane coupling agent includes at least one of 3-aminopropyltriethoxysilane and N-2-aminoethyl-3-aminopropyltriethoxysilane.
6. The negative electrode sheet according to any one of claims 1-5, characterized in that, The mass percentage of the sulfide solid electrolyte in the negative electrode active layer is 8-20%; And / or, the mass percentage of the negative electrode active material in the negative electrode active layer is 45-70%.
7. The negative electrode sheet according to any one of claims 1-5, characterized in that, The negative electrode active material includes a silicon-carbon material, which includes porous silicon and a carbon coating layer covering at least a portion of the surface of the porous silicon.
8. The negative electrode sheet according to claim 7, characterized in that, The thickness of the carbon coating layer in the silicon-carbon material is 2-10 nm; And / or, the porous silicon in the silicon-carbon material has a particle size Dv50 of 100-250 nm and a porosity of 55-65%.
9. The negative electrode sheet according to any one of claims 1-5, characterized in that, The negative electrode active layer further includes a conductive agent, which includes a first conductive agent and / or a second conductive agent; The first conductive agent comprises porous carbon, which includes mesopores and macropores. The macropores account for 15-45% of the total pore volume of the porous carbon. The main peak of the mesopores is located at 5.2 nm, and the main peak of the macropores is located at 85 nm. The second conductive agent includes at least one of conductive graphite, conductive carbon black, and carbon nanotubes.
10. The negative electrode sheet according to claim 9, characterized in that, The conductive agent includes the first conductive agent and the second conductive agent, and the mass ratio of the first conductive agent to the second conductive agent is 30:4 to 15:1; And / or, the mass percentage of the conductive agent in the negative electrode active layer is 16-34%.
11. The negative electrode sheet according to any one of claims 1-5, characterized in that, The negative electrode active layer further includes a binder, and the mass percentage of the binder in the negative electrode active layer is 2-6%, and the binder includes polyimide binders.
12. An all-solid-state battery, characterized in that, Includes the negative electrode sheet as described in any one of claims 1-11.
13. An electrical appliance, characterized in that, Includes the battery as described in claim 12.